(untitled) (Universal International Scientific Journal, 2026)
This article analyzes research on nonverbal communication, aiming to determine whether nonverbal behaviors are determined by innate human patterns or are primarily shaped by cultural experience. In the 20th century, the prevailing approach was to view nonverbal communication as entirely culturally dependent, and to explain observed cultural differences by specific notions of space and time